Setting up a new Radiology Center Technology for improvement : Data mining (Image Mining Technique) - Zubir, Nazira (2016)
Plethoric data produced by healthcare transactions are voluminous to be processed and too complex to be analysed by traditional method. The current technology development in data mining is gaining new momentum among health practitioners and researchers for example to improve diagnostic accuracy, identifying high risk patients and tracking concepts from unstructured data. In setting up a new Radiology Centre, the data mining technology specifically image mining is addressed. Data mining is the process of mining the hidden patterns from the huge data. Data mining scans a huge volume of data to find out the patterns and correlations among the patterns. Data mining requires the use of data analysis tool containing statistical model, mathematical algorithms and machine learning methods to determine previously unknown, valid patterns and relationships in huge volume data. The latest development of data mining in the field of biomedical imaging integrates the fuzzy logic, neural network and expert system. This development is very promising indeed as to provide the efficient and precise diagnosing platform for the cancer patients or patients who suffer from other diseases. The outline of how the systems could be integrated in the image mining for instance in diagnosing lung cancer is discussed. The examples of image processing and classification techniques used for predicting lung cancer are summarized. The similar techniques can be adopted to diagnose other types of cancer for examples breast and brain cancers.